Altered Neocortical Gene Expression, Brain Overgrowth and Functional Over-Connectivity in Chd8 Haploinsufficient Mice. (13th April 2018) - Suetterlin, Philipp; Hurley, Shaun; Mohan, Conor; Riegman, Kimberley L H; Pagani, Marco; Caruso, Angela; Ellegood, Jacob; Galbusera, Alberto; Crespo-Enriquez, Ivan; Michetti, Caterina; Yee, Yohan; Ellingford, Robert; et al.
Abstract: Truncating CHD8 mutations are amongst the highest confidence risk factors for autism spectrum disorder (ASD) identified to date. Here, we report that Chd8 heterozygous mice display increased brain size, motor delay, hypertelorism, pronounced hypoactivity, and anomalous responses to social stimuli. Whereas gene expression in the neocortex is only mildly affected at midgestation, over 600 genes are differentially expressed in the early postnatal neocortex. Genes involved in cell adhesion and axon guidance are particularly prominent amongst the downregulated transcripts. Resting-state functional MRI identified increased synchronized activity in cortico-hippocampal and auditory-parietal networks in Chd8 heterozygous mutant mice, implicating altered connectivity as a potential mechanism underlying the behavioral phenotypes. Together, these data suggest that altered brain growth and diminished expression of important neurodevelopmental genes that regulate long-range brain wiring are followed by distinctive anomalies in functional brain connectivity in Chd8 +/ − mice. Human imaging studies have reported altered functional connectivity in ASD patients, with long-range under-connectivity seemingly more frequent. Our data suggest that CHD8 haploinsufficiency represents a specific subtype of ASD where neuropsychiatric symptoms are underpinned by long-range over-connectivity.